2017
DOI: 10.1080/15348458.2017.1328281
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Minority Language Isolation: Translanguaging in a Trilingual School in the Basque Country

Abstract: Learning two or more languages at school is quite common all over Europe, but languages are often isolated from each other. This pedagogical practice is in contrast to the way multilingual speakers use their whole linguistic repertoire when communicating in social contexts. These multilingual solitudes are challenged when translanguaging pedagogies are used and multilingual students are allowed to use the resources in their linguistic repertoire. The specific focus of this article is to examine translanguaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 18 publications
1
57
0
10
Order By: Relevance
“…The languages involved in these studies are Indo‐European and their vocabularies are more likely to be related but pedagogical translanguaging can also include non‐Indo‐European languages such as Basque. Leonet, Cenoz, and Gorter (2017) report a study where compounds in Basque, Spanish and English are compared and the similarities and differences in their structure is compared.…”
Section: Pedagogical Translanguaging and Metalinguistic Awarenessmentioning
confidence: 99%
“…The languages involved in these studies are Indo‐European and their vocabularies are more likely to be related but pedagogical translanguaging can also include non‐Indo‐European languages such as Basque. Leonet, Cenoz, and Gorter (2017) report a study where compounds in Basque, Spanish and English are compared and the similarities and differences in their structure is compared.…”
Section: Pedagogical Translanguaging and Metalinguistic Awarenessmentioning
confidence: 99%
“…They concluded that translanguaging, understood in the original Welsh way as using different languages for input and output, was a useful tool because it facilitated the understanding of content. The potential benefits of pedagogical translanguaging have also been highlighted by Canagarajah (2011) or Leonet, Cenoz, and Gorter (2017).…”
Section: Morphological Awareness and Translanguagingmentioning
confidence: 99%
“…O modo como se concebe a aprendizagem da L2 ou L3 tem subjacente representações sobre as línguas (L1, L2, L3) e pode estar eivado de ideologia (Conteh & Meier, 2014). Conceber o conhecimento linguístico de mais do que uma língua como a integração de sistemas mais do que como sistemas isolados de conhecimento, aproxima-se do que se pensa ser o modo de agir dos falantes multilingues (Aronin, 2019;Leonet, Cenoz, & Gorter, 2017;Lewis, Jones & Baker, 2012). E pode transformar-se numa ferramenta pedagógica valiosa ao mobilizar os reportórios linguísticos dos estudantes para desenvolver a consciência linguística, o conhecimento metalinguístico e competências comunicativas e académicas em várias línguas (Leonete t al., 2017).…”
Section: Língua Materna (L1)unclassified